Pre-Service Teachers’ Performance-Input: Development Program in the New Normal - Nayad, Menchi Guande (Jurnal Pendidikan Progresif, 2023)
Pre-service Teachers’ Performance-Input: Development Program in the New Normal.  Objectives:  The study investigates the level of performance of pre-service teachers particularly on communication, technical, lesson Planning, evaluation, classroom management, time management and occupational attitude skills and establishes if there is a significant difference between the level of performance of pre-service teachers as perceived by the three groups of respondents. Methods. A questionnaire on the Likert scale collected data through the survey method from 100 resource teachers, 103 pre-service teachers and 500 high school students. Weighted means, ANOVA and Scheffe’s test were utilized to analyze the data gathered.    Findings. Results revealed that the performance of pre-service teachers was generally perceived to be very satisfactory, a significant difference on the level of performance of pre-service teachers was established as perceived by the three group of respondents.  Conclusion.  Pre-service teachers performed well on the specific tasks assigned to them and they have met the respondents’ expectations and the responsibilities expected of them. Keywords:  new normal, occupational attitude, pre-service teachers, resource teachers, technical skillDOI: http://dx.doi.org/10.23960/jpp.v13.i2.202321